Sedimentology and Stratigraphy of a Large, Pre-Vegetation Deltaic Complex - Jones, Robyn; Marcelissen, Rachel; Fralick, Philip (Frontiers in Earth Science, 2022)
The operation of depositional processes in fluvial systems prior to the development of land-based, macrophyte vegetation has undergone considerable research. The differences in sedimentation in the channels and floodplains compared to post-vegetation systems should result in differences also existing in the deposits developed where the rivers debouch their loads into standing bodies of water. These deltaic deposits have been studied relatively less. The 1.4 Ga Kama Hill and Outan Island Formations of the Sibley Group, northwestern Ontario, provide a site to further investigate these potential differences. Four totally cored drill holes intersect this 340 m thick, prograding, deltaic to fluvial succession. It is divisible into eight lithofacies associations representing environments ranging from prodelta to the delta-top floodplain-channel assemblage. The sub-aqueous portion of the successions is composed of two thick progradational delta lobes recording the progression from maximum flooding surface to lowstand systems track. This was probably caused by: depositional regression and development of a condensed sequence due to channel avulsion with distal repositioning, and finally channel avulsion with proximal repositioning driving another depositional regression. At a smaller scale, members of progradational parasequence sets decrease in thickness from the prodelta to upper distributary-mouth bars. The deltaic deposits are compared to the modern, large Mississippi deltaic system. Sub-aqueous sub-environments contain similar deposits, with the exception: 1) the lack of infauna bioturbation leads to better preservation of Sibley Delta sedimentary structures; 2) scarce organic sediment does not allow reducing diagenetic reactions, thus preserving the highly oxidized nature of the fluvial sediments; 3) the Sibley distributary-mouth bars have more medium- and coarse-grained sand than the Mississippi bars; 4) the Sibley distributary-mouth bars have abundant thick, massive, non-graded, normal graded and reverse graded sandstones, likely the result of high-discharge slurry-flows from the fluvial channels; 5) the lack of macrophytes (coastal marshes) complicates interpreting the transition from bar tops to sub-aerial environments; 6) the abandonment phase of bay-fill progradational parasequences is further condensed due to the lack of organic deposits. However, the considerable similarities between the Sibley Delta and the Mississippi Delta denote that not all pre-vegetation deltas conform to general braid and fan delta models.